2017
DOI: 10.4317/jced.53704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemostatic agent on marginal gaps of class V giomer restorations

Abstract: BackgroundContamination of dentin with hemostatic agents might exert a deleterious effect on adhesive procedures on dentin. The present study was undertaken to investigate the effect of aluminum chloride hemostatic agent on marginal gaps in Cl V giomer restorations.Material and MethodsFifty sound bovine permanent incisors were selected for the purpose of this in vitro study and Cl V cavities were prepared on their buccal surfaces; the gingival margins of the cavities were placed in dentin. The tooth samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Tests conducted by Kimyai [33] show that contamination with hemostatic agents can increase the microleakage and marginal gaps in giomer restorations [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tests conducted by Kimyai [33] show that contamination with hemostatic agents can increase the microleakage and marginal gaps in giomer restorations [33].…”
Section: Discussionmentioning
confidence: 99%
“…The shrinkage of the giomer (Beautifil II) was lower than Fuji II LC when using low mode [26] . It is important to avoid disinfecting the cavity with chlorhexidine before applying the material [27] or contact with aluminum chloride (in class V cavities) because it increases the space between the material and the tooth [28] . Nevertheless, it has high quality mechanical and optical properties [29] .…”
Section: Physical Properties 331 Giomermentioning
confidence: 99%
“…Giomers are a new group of composite materials composed of pre-reacted glass-ionomer fillers in a resin matrix; they have some advantages, including the release of fluoride ions and recharging, similar to glass-ionomers, in conjunction with other properties of composite resins, such as optimal esthetics, polishability, and tissue compatibility [ 10 , 11 ]. A study reported that the use of 15% carbamide peroxide increased the surface roughness of giomer, with no change in its color [ 12 ].…”
Section: Introductionmentioning
confidence: 99%